2017
DOI: 10.2337/db17-0118
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Protein UCP2 Controls Pancreas Development

Abstract: The mitochondrial carrier uncoupling protein (UCP) 2 belongs to the family of the UCPs. Despite its name, it is now accepted that UCP2 is rather a metabolite transporter than a UCP. UCP2 can regulate oxidative stress and/or energetic metabolism. In rodents, UCP2 is involved in the control of α- and β-cell mass as well as insulin and glucagon secretion. Our aim was to determine whether the effects of UCP2 observed on β-cell mass have an embryonic origin. Thus, we used knockout mice. We found an increased size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…This increase may be correlated with the energy demand during the differentiation of the duct cells, lumen formation, and tubulogenesis. Mitochondria are important systems producing energy in all vertebrate cells (Chan, ) and it is suggested that they play a significant role in pancreas morphogenesis (Broche et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This increase may be correlated with the energy demand during the differentiation of the duct cells, lumen formation, and tubulogenesis. Mitochondria are important systems producing energy in all vertebrate cells (Chan, ) and it is suggested that they play a significant role in pancreas morphogenesis (Broche et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Uncoupling proteins (UCPs) are closely associated with IMM potential (44,45). Complexes I-IV in the ETC pump protons from the mitochondrial matrix into the IMM and the intermembranous space to establish a H + gradient, whilst UCPs (particularly UCP-1) in the IMM facilitate proton leakage to reduce the IMM potential, uncoupling the respiratory process from ADP phosphorylation (42,46). During this process, UCPs render the final products derived from electron transport to be heat instead of ATP ( Fig.…”
Section: Mitochondria-related Genomic and Proteomic Abnormalitiesmentioning
confidence: 99%
“…The potential role of UCPs in the modulation of insulin secretion in response to glucose has been the focus of research attention. UCP-2 is a negative regulator during pancreatic development (46) and silences glucose oxidation in β-cells, which is the initial process of GSIS (94). Previous studies have demonstrated that upregulated UCP-2 and downregulated UCP-3 under chronic high glucose conditions impaired GSIS in β-cells (43,95).…”
Section: Association Between Mitochondrial Dysfunction and Islet β-Cementioning
confidence: 99%
“…Uncoupling protein 2 (UCP2), a member of mitochondrial transporters family, has been reported to be involved in metabolic reprogramming [17,18]. The ability of UCP2 to regulate glucose is strongly associated with cellular proliferation and apoptosis [19].…”
Section: Introductionmentioning
confidence: 99%